АНАЛИЗ МЕРОПРИЯТИЙ ПО ВНУТРИКОНТУРНОМУ ЗАВОДНЕНИЮ МЕСТОРОЖДЕНИЯ “ЖАНАЖОЛ” ДЛЯ ПОВЫШЕНИЯ НЕФТЕОТДАЧИ ПЛАСТОВ (World Science, 2016)
In this article, "of measures to contour waterflooding fields Janajol FOR EOR" describes the ways and means to enhance oil recovery.